1989
DOI: 10.1038/340061a0
|View full text |Cite
|
Sign up to set email alerts
|

Very high frequency of lymphoma induction by a chemical carcinogen in pim-1 transgenic mice

Abstract: Infection of mice with Moloney murine leukaemia virus (MuLV) induces T-cell lymphomas after an average latency period of 150 days. In these lymphomas the MuLV DNA is frequently integrated into the mouse chromosomal DNA in the vicinity of the pim-1 oncogene. Transgenic mice overexpressing the pim-1 oncogene are predisposed to develop T-cell lymphomas, but only to the extent that approximately 10% of the mice develop a lymphoma within 240 days. When these mice are infected with MuLV, lymphomas develop in all mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 15 publications
5
83
0
Order By: Relevance
“…During the latent period, additional genetic changes may be required to convert the proliferating thymocyte to a malignant cell. This process may be similar to those observed in murine lymphomas induced by chemicals (Newcombe et al, 1988;Breuer et al, 1991;Corominas, et al, 1991), oncogenes (Breuer et al, 1991;Lindeman al., 1994;Linette et al, 1995), or tumor suppressor gene mutant mice (Donehower et al, 1992;Angel et al, 1993;Elson et al, 1995).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…During the latent period, additional genetic changes may be required to convert the proliferating thymocyte to a malignant cell. This process may be similar to those observed in murine lymphomas induced by chemicals (Newcombe et al, 1988;Breuer et al, 1991;Corominas, et al, 1991), oncogenes (Breuer et al, 1991;Lindeman al., 1994;Linette et al, 1995), or tumor suppressor gene mutant mice (Donehower et al, 1992;Angel et al, 1993;Elson et al, 1995).…”
Section: Introductionsupporting
confidence: 74%
“…MNU also increased the incidence of mammary tumors in mice transgenic for MMTV-N-ras (Mangues et al, 1994). Likewise, ethylnitrosourea increases lymphomagenesis in pim-1 transgenic mice through myc overexpression and, in 10% of cases, K-ras mutations (Breuer et al, 1991). In a skin tumor initiation/promotion model, heterozygotic p53 knockout mice had an increased incidence of carcinomas but a similar incidence of papillomas following MNU exposure, suggesting a role for the heterozygotic state of p53 in cancer promotion but not initiation (Kemp et al, 1993).…”
Section: Discussionmentioning
confidence: 94%
“…This suggested that overexpression of the pim-1 gene by itself was insu cient for cell transformation. Accordingly, when Em-pim-1 mice were exposed to viral or chemical carcinogenic agents, the development of lymphomas was accelerated Breuer et al, 1989). In most cases, this correlated with activation of one of the myc family oncogenes.…”
Section: Introductionmentioning
confidence: 99%
“…Its expression is induced by a variety of cytokines, growth factors, and mitogens (17)(18)(19), suggesting that Pim-1 may be an important intermediate in signal transduction. In hematopoietic cells, Pim-1 cooperates with c-Myc (20,21) and enhances the transcription activity of c-Myb (22,23). It has also been shown that Pim-1 activates the cyclin-dependent kinase inhibitor p21 (24) and that the antiapoptotic factor Bcl-2 is regulated downstream of Pim-1 (25), suggesting that Pim-1 is involved in cell cycle regulation and apoptosis in hematopoietic cells.…”
mentioning
confidence: 99%